2005
DOI: 10.1002/cncr.20842
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cytokine genotypes on the hepatitis B virus‐hepatocellular carcinoma association

Abstract: BACKGROUND In Southern Guangxi, China, chronic infection with the hepatitis B virus (HBV) acquired during the perinatal period from carrier mothers is a primary cause of hepatocellular carcinoma. However, only a minority of HBV carriers eventually develop hepatocellular carcinoma. The authors hypothesized that cytokine genotypes may be important codeterminants of the risk of HBV‐related hepatocellular carcinoma. METHODS The authors examined the correlation between polymorphisms in T‐helper 1 (Th1) and Th2 cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 51 publications
4
74
2
Order By: Relevance
“…In this study, we found that individuals with four to six risk genotypes (i.e., IL-2-330AA, IFN-γ-1615AG/ AA, IL-1β-511CT/TT, IL-1β-1464CG/GG, IL-6-572GG/ CG, and IL-10-592TG/GG) may have an increased HCC risk. Consistent with the result of Nieters et al (2005), the present study found that the synergistic rather than the individual effects of cytokine gene SNPs were associated with an increased HCC risk.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we found that individuals with four to six risk genotypes (i.e., IL-2-330AA, IFN-γ-1615AG/ AA, IL-1β-511CT/TT, IL-1β-1464CG/GG, IL-6-572GG/ CG, and IL-10-592TG/GG) may have an increased HCC risk. Consistent with the result of Nieters et al (2005), the present study found that the synergistic rather than the individual effects of cytokine gene SNPs were associated with an increased HCC risk.…”
Section: Discussionsupporting
confidence: 90%
“…The designs of the 2 studies have been described previously. 8,29 Permission to conduct this study had been obtained from the Institutional Review Boards at the University of Southern California and the Guangxi Cancer Institute. Separate informed consent forms for interview and biospecimen collection were obtained from each study participant.…”
Section: Methodsmentioning
confidence: 99%
“…The assays used for testing serologic markers of HBV and HCV infections have been described previously. 8, 29 Briefly, we tested all study samples for the presence of hepatitis B surface antigen in serum using commercialized kits (AUSRIA, Abbott Laboratories, North Chicago, IL), and negative samples (for the Los Angeles study only) were further tested for the presence of antibodies to the hepatitis B core antigen using standard testing kits (Corab, Abbott Laboratories, North Chicago, IL). All samples were tested for the presence of antibodies to the hepatitis C virus (anti-HCV) in serum using the enzyme linked immunosorbent assay version 2.0 kit manufactured by Ortho Diagnostic Systems, with confirmation of positive samples using RIBA version 2.0 (Chiron, Emeryville, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, when carrying fusion peptides, Lmdd is able to elicit a T-cell response against various epitopes simultaneously. In HCC patients, it has been demonstrated that a deviation to a Th2 immune response occurs (Nieters et al, 2005). In our Tg animals, vaccination with Lmdd-MPFG led to a shift in the Th1/Th2 balance toward a Th1 dominant immune response, as demonstrated by the increased secretion of the Th1 cytokine IFN-g in the stimulated splenocytes by ELISA and ELISPOT assays.…”
Section: Listeria-based Vaccine Against Hccmentioning
confidence: 51%